MODELLING DYNAMICS OF ZNO PARTICLES IN THE SPRAY PYROLISIS REACTOR TUBE - Diky Anggoro; Melania Muntini; Iim Fatimah; Sudarsono Sudarsono (UNEJ e-Proceeding, 2016)
Development of ZnO particles research is current quite rapidly, especially in the fields of medicine and energy. ZnO Particle morphology during the process of synthesis using spray pyrolysis systems highly influential in its application the future. Our research group has developed a system of tubes spray pyrolysis reactor with the electrical heater. Physical phenomena that occur in the processing of particles, simulated in the form of a mathematical equation, useful for the experimental spray pyrolysis as there some parameters such as carrier gas flow (Q), the temperature of reactor walls (Tw), the number concentration of droplets that enter reactor (No), and the size of initial droplet diameter (dPo). The modelling parameters provide system optimization and prediction of particle morphology formed from experiments.